A hydraulic hybrid excavator based on multi-chamber cylinders and secondary control – design and experimental validation. Issue 2 (4th May 2018) - Heybroek, Kim; Sahlman, Mika
Abstract: In this paper, a special type of multi-chamber cylinders along with secondary controlled hydraulic motors are key components in the design of a highly efficient hydraulic series hybrid system. The system is developed for and tested on a large excavator (30-ton class). The evaluated system supports potential and kinetic energy recovery and storage using hydraulic accumulators. Through proper sizing of components and sophisticated valve control, an energy-efficient, flexible and robust hybrid system is achieved. The study describes how the demonstrator is tested in real truck loading cycles. A detailed energy analysis is also presented to explain the energy flow inside the hybrid system.